Apoyo en la secretaría de infraestructura correspondiente en supervisión de obra y elaboración de documentos en la alcaldía de Belén, Boyacá (2022)
The following report carried out as a degree project is presented in an internship modality for the civil engineering faculty of the Antonio Nariño University (UAN) and has the purpose of providing support in the corresponding infrastructure secretariat in supervision of work and preparation of documents. in the mayor's office in Belén, Boyacá; Among the documents mentioned above, minutes were found for contracts such as start, termination, suspension, final re ceipt and liquidation, among others, and regarding the supervision of works such as in the tertiary roads of the municipality.